The use of supply chain operations reference (SCOR) in measuring the performance of supply chain management in agribusiness sector - Wirda, Bunga; Irwandi, Putra; Muflikh, Yanti Nuraeni; Nurmalina, Rita (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: This article uses a literature review study approach sourced from previous research and relevant to the topic of this research, namely the Supply Chain Operation Reference (SCOR) model. This research aims to (1) analyze the trend of SCOR Model research in the field of Agribusiness (2) identify supply chain management performance indicators (3) identify variables considered in measuring supply chain management performance (4) analyze the effectiveness of SCOR in measuring supply chain management performance, especially in the field of Agribusiness. Methods: This study conducted a literature review of 32 articles from 2014-2023 in the fields of management, business, and agriculture. Data analysis used bibliometrics and Systematic Literature Review sourced from the Scopus database with the help of VOSviewer and R-Studio software. Results: The results showed that the trend in the number of SCOR model studies fluctuated, which was dominated by articles sourced from Scopus with the main keywords that appeared were Supply Chain Management and SCOR Model. All articles carried out four main business processes namely Plan, Source, Make, and deliver with the priority of reliability attributes as the main improvement priority. Conclusion: Most of the supply chain performance levels of the articles analyzed are in the average category.